PERANAN PEMBERIAN KREDIT PERTANIAN BANK BRI TERHADAP PENDAPATAN PETANI WORTEL DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR - Rianita O. Rares; Joachim N.K. Dumais; Charles R. Ngangi; Noortje M. Benu (Universitas Sam Ratulangi, 2015)
ABSTRACT Giving credit program with the intermediary of bank aims to add capital farmers so that they can expand their business. Farmers need more capital obtained through loans, in order to develop farming, so that the results of farming can increase. Problems faced by farmers in Rurukan that farmers have not been able to optimize its production because of capital constraints that hindered farmer’s income could not increase. Based on the description above, the problem in this research is how the role of agricultural credit from BRI Bank to the income of carrot’s farmers in Rurukan villages. The objective of this research is to analyze the role of agricultural credit from BRI Bank to the income of carrot farmers in Rurukan villages. The method used is descriptive based on survey research area. The research result showed that loans received by farmers from banks is used for the addition of the factors of production used by farmers as increasing the number of labor, increase the use of fertilizers, seeds and tools, so that production of farmer could increase. The increase in production has resulted in increasing farmer's income as well. So it can be seen that there is a difference between the income of carrot’s farmer before receiving credit and after receiving credit. In other words, credit borrowed from banks have a positive impact on carrot’s farming activities. Keywords : Giving Credit Program And Farmer’s Income